The Educational Management Model of Child Development Center Under SubDistrict Administrative Organization in Nan Province - ขจรพงศ์กีรติ เชาวฤทธิ์ (Community and Social Development Journal, 2015)
This dissertation was intended to develop the educational management model of child development center Under subdistrict administrative organization in Nan province. And examined the possible adoption of the educational management model of child development center under subdistrict administrative organization in Nan province. The sample consisted of 358 personnel in subdistrict administrative organization in Nan province included Chief Executive of subdistrict administrative organization, Chairman of subdistrict administrative organization, Permanent of subdistrict administrative organization, Director of Education Religious and Culture division and Chief of child development center. To examine the possible adoption of the educational management model of child development center under subdistrict administrative organization in Nan province by five experts. The instruments used to collect data included an interview and questionnaire. Data analysis were using computer programs for the extraction factors (Factors Analysis), correlation coefficient between variables, confirmatory factor analysis by axial rotation method (Varimax) to determine the factors (Components). The results of study found that. 1. The educational management model of child development center under subdistrict administrative organization in Nan province, in the opinion of personnel of subdistrict administrative organization in Nan province were six factors, including the first factor; the participation and support of all sectors and experience with 48 components. The second factor; the premises and environment with 25 components, the third factor; personnel, finance and procurement were 12 elements. The fourth factor; experienced were 13 elements The fifth factor; nutrition, hygiene with 10 elements and the sixth factor; measurement and Assessment with 10 elements. 2. The educational management model of child development center under subdistrict administrative organization in Nan province were the format consists of management patterns of child development center at six key elements, that were reasonably accurate as possible, and could put to practical used. This was consistent with the conceptual framework as the theory of research.